2005
DOI: 10.3354/meps292181
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Thaliacea in SW Taiwan coastal water in 1997, with special reference to Doliolum denticulatum, Thalia democratica and T. orientalis

Abstract: Diel vertical migration of Thaliacea was monitored during different seasonal cruises in 1997 in the southwestern waters of Taiwan using samples collected by multiple plankton sampling nets and a 1 m plankton net. Overall, Doliolum denticulatum, Thalia democratica and T. orientalis were the 3 most dominant species in all seasons, and contributed ≥ 93% of the numerical total of Thaliacea. These species exhibited about a 2 times higher abundance at night than during the day, if all the data were integrated. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 30 publications
5
9
1
Order By: Relevance
“…This is supported by both 'normal' and reverse T. democratica DVM on different sampling days during individual blooms in both 1996 and 2011. Other studies in the Agulhas Bank (Gibbons 1997), off SW Taiwan (Tew & Lo 2005), and in the Kuroshio Current (Tsuda & Nemoto 1992) found that T. democratica did not exhibit DVM and generally stayed within the upper 200 m. Thus, we conclude that the diel differences we detected in T. democratica were likely due to bloom patchiness and that T. democratica likely does not undergo significant DVM.…”
Section: Diel Vertical Migrationsupporting
confidence: 49%
See 1 more Smart Citation
“…This is supported by both 'normal' and reverse T. democratica DVM on different sampling days during individual blooms in both 1996 and 2011. Other studies in the Agulhas Bank (Gibbons 1997), off SW Taiwan (Tew & Lo 2005), and in the Kuroshio Current (Tsuda & Nemoto 1992) found that T. democratica did not exhibit DVM and generally stayed within the upper 200 m. Thus, we conclude that the diel differences we detected in T. democratica were likely due to bloom patchiness and that T. democratica likely does not undergo significant DVM.…”
Section: Diel Vertical Migrationsupporting
confidence: 49%
“…m −3 , which is comparable to a S. fusiformis maximum of 1.6 ind. m −3 in coastal Taiwan (Tew & Lo 2005) and 2 ind. m −3 in the Humboldt Current (González et al 2000).…”
Section: Salp Species Composition and Seasonalitymentioning
confidence: 99%
“…S1g-j in the Supplement). These findings are in agreement with other studies that found populations mostly dominated by females in autumn and winter samples (Heron & Benham 1985, Tew & Lo 2005. Interestingly Heron & Benham (1985) also observed that blastozooids were not reproducing, although they concluded that, in the typical situation for population latency (what they called 'overwintering'), oozooids arrested their growth while retaining their chains until the onset of favourable conditions.…”
Section: Stages Contributing To Population Growth Under Contrasting Csupporting
confidence: 90%
“…Dives, for example, showed a doliolid abundance decreasing by two orders of magnitude over a vertical distance of only 2 m (Paffenhöfer et al 1991). However, time-series suggest that the depth where reproduction takes place and thaliacean stages are distributed seasonally, may be related to environmental variables such as temperature, salinity and food (Licandro et al 2006), depending on species (Paffenhöfer et al 1995;Tew and Lo 2005). But the coupling may be subject to environmental disturbance as examplified by the conspicuous mesopelagic findings of thaliaceans at site C (see above).…”
Section: Vertical Distribution and Migrationmentioning
confidence: 99%